User Acceptance pada Pengguna Aplikasi Mobile Payment Ovo - Irsyad Aslam; Jaryono Jaryono; Suci Indriati (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
An associative and quantitative research study through survey method, on every individual who uses OVO mobile payment application on their respective phone that lived in Purwokerto, Jawa Tengah. The title of this research are “User Acceptance of OVO Mobile Payment Application Users (Case Study in Purwokerto, Jawa Tengah)”.The aim of this research was to analyze the user acceptance of OVO mobile payment application users in Purwokerto, Jawa Tengah, by examing the influence of performance expectancy, effort expectancy, facilitating conditions, habit, price value, hedonic motivation, against behavioral intention to use, which moderated by age. This research’s population are every men and women who lives in Purwokerto, Jawa Tengah, who uses OVO mobile payment. Based on prior survey, this research took a huge amount of participants, consists of 133 respondents, which gained by using the purposive sampling method. Refers to the research results and data analysis, using the PLS-SEM analysis, shown that: (1) performance expectancy is insignificant on behavioral intention to use, (2) effort expectancy has a positive effect on behavioral intention to use, (3) facilitating conditions is insignificant on behavioral intention to use, (4) habit has a positive effect on behavioral intention to use, (5) price value gives a positive effect on behavioral intention to use, (6) hedonic motivation gives a positive effect on behavioral intention to use. Furthermore, according to the moderating hypotheses results, it concluded that user’s age moderates and enhance the positive effect of effort expectancy, habit, and hedonic motivation, whereas performance expectancy, facilitating conditions, and price value are not moderated and enhanced by the user’s age. Based on prior explanation, OVO company should improve their application’s performance, provide a better support for the customer (e.g. customer support), and also differentiate their services and promos in order to gain potential customers from every age group in society.